The potential of combined immunotherapy and antiangiogenesis for the synergistic treatment of advanced NSCLC - Manegold, Christian (Journal of thoracic oncology, 2017)
Over the past few years, there have been considerable advances in the treatments available to patients with metastatic or locally advanced NSCLC, particularly those who have progressed during first-line treatment. Some of the treatment options available to patients are discussed here, with a focus on checkpoint inhibitor immunotherapies (nivolumab and pembrolizumab) and antiangiogenic agents (bevacizumab, ramucirumab, and nintedanib). It is hypothesized that combining immunotherapy with antiangiogenic treatment may have a synergistic effect and enhance the efficacy of both treatments. In this review, we explore the theory and potential of this novel treatment option for patients with advanced NSCLC. We discuss the growing body of evidence that proangiogenic factors can modulate the immune response (both by reducing T-cell infiltration into the tumor microenvironment and through systemic effects on immune-regulatory cell function), and we examine the preclinical evidence for combining these treatments. Potential challenges are also considered, and we review the preliminary evidence of clinical efficacy and safety with this novel combination in a variety of solid tumor types.
Available online 8 October 2016
Gesehen am 12.09.2018